A dimensionless analysis of radial heat conduction with variable external convection boundary conditions - Branco, J. F. (2001)
Radial heat conduction in insulated pipes under external convection is usually dealt with great detail in several heat transfer publications. However, an analysis carried out through the graphical representation of the dimensionless characteristic parameters, will allow a better understanding of the phenomenon. Here the dependence of the convection coefficient on the external radius and external surface temperature, typical of forced and free convection, is taken into account. Assuming a power law variation of the convection coefficient [1] and using the results of Sparrow [2], all the important dimensionless parameters, including the critical radius, are explicitly represented and compared with those arising in the case of the insulated sphere [3].